Children's Understanding and Use of Four Dimensions of Social Status - Enright, Elizabeth A.; Alonso, Daniel J.; Lee, Bella M.; Olson, Kristina R. (Journal of cognition and development, 2020)
Beginning early in life, children are exposed to people who differ in social status. In five studies, we investigate whether 3- to 6-year-old children recognize different dimensions of status (i.e., wealth, physical dominance, decision-making power, and prestige) and use these dimensions to inform their social judgments (preferences and resource allocation). Across studies, we found that by age 3, children identify high-status people as in-charge. Further, while 3-6-year-olds favor higher status individuals over lower status individuals on a preference measure, 5-6-year-olds allocate a resource to a lower status individual over a higher status individual and 3-4-year-olds are at chance in their allocation. We observed minimal differences across dimensions of status in these studies. Taken together, across five pre-registered studies, we demonstrated that children identify and use social status distinctions to inform their social judgments across a variety of different dimensions.